ENHANCING INCIDENTAL VOCABULARY ACQUISITION THROUGH GLOSSING AND GALLERY WALK IN INDONESIAN HIGH SCHOOL ENGLISH AS A FOREIGN LANGUAGE (EFL) CONTEXT - Ritonga, Yesi Nuraini; Devanti, Yeni Mardiyana; Hidayati, Kuni Hikmah (Universitas Muhammadiyah Metro, 2026)
This study investigates the effectiveness of integrating glossing and Gallery Walk to enhance incidental vocabulary acquisition in secondary EFL classrooms. The primary issue in vocabulary learning in English classes is the reliance on memorization methods, which can lead to students becoming less motivated and hindering their ability to retain new vocabulary. However, limited studies have examined the integration of glossing strategies within interactive classroom practices, particularly in the Indonesian secondary Foreign Language in English learning contexts. This study employed an action research design following the model proposed by Kemmis and McTaggart (1988), conducted in two cycles, involving ten eleventh-grade students at a private secondary school in Jember Regency. The learning activities integrate the gloss strategy in reading with the steps of a Gallery Walk. Data were collected through pre-tests, post-tests, and classroom observations, and analyzed using comparative quantitative and qualitative approaches. The results demonstrate progressive improvement in vocabulary achievement and student engagement across cycles, suggesting that integrating glossing and Gallery Walk effectively supports incidental vocabulary acquisition and learner motivation. These results provide practical implications for vocabulary teaching in secondary EFL classrooms.